2006
DOI: 10.1126/science.1120519
|View full text |Cite
|
Sign up to set email alerts
|

Cell Type Regulates Selective Segregation of Mouse Chromosome 7 DNA Strands in Mitosis

Abstract: After chromosome replication, sister chromatid copies are generally thought to segregate randomly to daughter cells. However, sister chromatids differ in their DNA strands, with each chromatid inheriting one older strand that is paired to a newly synthesized strand. Genetic analysis with a homologous chromosome pair indicated nonrandom chromatid distribution in embryonic stem cells. Biased segregation pattern was also found in all 100 endoderm cells examined, but not in any of the 165 neuroectoderm cells. In c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
99
5
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(111 citation statements)
references
References 17 publications
5
99
5
2
Order By: Relevance
“…We suggest that strandspecific imprinting along with nonrandom segregation mechanisms may have evolved as one of the avenues to produce multiple arrays of cell types in higher eukaryotes (Klar 2004b). In mouse embryonic stem cells, the data indicates that parental chromosome 7 Watson strands always co-segregate to the same daughter cell leaving Crick strands to go to the sister cell (Armakolas and Klar 2006;Armakolas and Klar 2007). Such biased chromatid segregation is proposed to be a mechanism for development in higher organisms (Klar 2008;Armakolas et al 2010;Sauer and Klar 2012).…”
Section: Discussionmentioning
confidence: 91%
“…We suggest that strandspecific imprinting along with nonrandom segregation mechanisms may have evolved as one of the avenues to produce multiple arrays of cell types in higher eukaryotes (Klar 2004b). In mouse embryonic stem cells, the data indicates that parental chromosome 7 Watson strands always co-segregate to the same daughter cell leaving Crick strands to go to the sister cell (Armakolas and Klar 2006;Armakolas and Klar 2007). Such biased chromatid segregation is proposed to be a mechanism for development in higher organisms (Klar 2008;Armakolas et al 2010;Sauer and Klar 2012).…”
Section: Discussionmentioning
confidence: 91%
“…Thus, different frequencies of LOH in particular cell types may be the consequence of the relative fraction of z segregation and may be related to the cell cycle compartment in which recombination occurs. Also, it could be related to variability of nonrandom segregation of original and newly replicated DNA strands [59] and may even vary between individual chromosome pairs within a specific single cell type. Thus, patterns of LOH might be directly related to organismal development and cell differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…One simple explanation is that the Trp53-/-epithelium contains less quiescent cells than wild type, which is possible considering the important role of p53 in regulation of cell cycle checkpoint and senescence. Another rather tempting explanation is that p53 may regulate the partition of sister chromatids during mitosis, which could be decisive for the fate of daughter cells 19 . We showed that p53 negatively regulated MaSCs self-renewal and that Trp53-/-epithelium contained more long-term regenerative MaSCs than wild type epithelium.…”
Section: Resultsmentioning
confidence: 99%